2020
DOI: 10.1177/1120672120957584
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between retinal nerve fiber layer thickness and IOP variation in glaucoma suspects and patients with primary open-angle glaucoma

Abstract: Purpose: To analyze the relationship between retinal nerve fiber layer thickness (RNFLT) and intraocular pressure (IOP) variation in glaucoma suspects (GS) and patients with primary open-angle glaucoma (POAG). Methods: Thirty-one GS and 34 POAG patients underwent ophthalmologic examination and 24-h IOP measurements. GS had IOPs ranging from 19 to 24 mmHg and/or suspicious appearance of the optic nerve. POAG patients had reproducible abnormal visual fields. We only included patients who presented with short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…(25) Cronemberger et al have studied the correlation between the thickness of the RNFL and the variation in IOP in suspected glaucoma and patients with POAG. (26) They concluded that IOP at 6:00 a.m. and ∆IOP had negative correlations with RNFL thickness quadrants in POAG. In suspected glaucoma, this negative correlation of RNFL thickness occurred between the IOP taken at 6:00 a.m. and the inferior quadrant.…”
Section: Adequate Intraocular Pressure Controlmentioning
confidence: 97%
See 1 more Smart Citation
“…(25) Cronemberger et al have studied the correlation between the thickness of the RNFL and the variation in IOP in suspected glaucoma and patients with POAG. (26) They concluded that IOP at 6:00 a.m. and ∆IOP had negative correlations with RNFL thickness quadrants in POAG. In suspected glaucoma, this negative correlation of RNFL thickness occurred between the IOP taken at 6:00 a.m. and the inferior quadrant.…”
Section: Adequate Intraocular Pressure Controlmentioning
confidence: 97%
“…These findings may indicate potential risk factors for glaucoma progression. (26) The Contact Lens Sensor (CLS) Sensimed Triggerfish® approved by the Food and Drug Administration (FDA) in 2016 has been used to detect IOP-related changes in one eye over a 24-hour period. (27) However, it does not give real IOP values and presents controversial results in relation to other methods of measuring IOP.…”
Section: Adequate Intraocular Pressure Controlmentioning
confidence: 99%